(untitled) (Docentes 2.0 Journal, 2021)
Local public institutions are immersed in a competitive environment; they test their internal and external environments. They must also constitute an institutional platform to implement public policies in response to the general interests of societies. This study was carried out to demonstrate intervention and research challenges in public administrations to document strategies, solve structural, functional, systemic problems, and strengthen their capacities through decisions that provide certainty to their collaborators. A combination approach of qualitative and quantitative interpretative analysis was used, applying diachronic, systematic, synchronous, structural methods to understand the role of the thinking of its protagonists. For this, social knowledge is deployed in the research archetype in public spheres. Their results showed that the intentions of professionalization were considered by governments as intricate long-term efforts, without benefits, entailing concrete short-term costs with long-term benefits. From the above, managers observed a reduction of flexibility to manage personnel under the principles of autonomy in this edge. On the other hand, second-line administrators expressed uncertainty about their permanence in the organizations. The professional profile does not guarantee a work stay; this scenario weakened the principles of consolidating institutional development. At the country level, 55 percent of local institutions do not have internal regulations. It means that managing knowledge tends to develop an organization in generating competitive attributes; it leads to building an organizational culture.